PELATIHAN PEMBUKUAN SEDERHANA UNTUK UMKM SEBAGAI UPAYA KETAHANAN EKONOMI DI MASA PANDEMI COVID-19 - Mufti Arief Arfiansyah; Edi Suminto (LPPM STAIMAS WONOGIRI, 2021)
The Covid-19 pandemic has resulted in a decrease in sales turnover for MSMEs. This impact greatly threatens economic resilience for the sustainability of MSME businesses. MSME actors need to be encouraged and assisted in order to be able to survive the Covid-19 pandemic. These countermeasures can be carried out through community service activities using direct observation methods in the community and tracing and analyzing the problems faced by MSME actors, especially economic resilience in the midst of the Covid-19 pandemic. STAIMAS Wonogiri Islamic Economics Study Program dedication aims to provide simple bookkeeping training for MSME actors during the Covid-19 pandemic. The targeted segmentation is MSME actors located in the Shower Environment, Kaliancar Village, Wonogiri District, Wonogiri Regency. The service activities ran smoothly and the participation of the participants was active and enthusiastic. In this simple bookkeeping training, participants were introduced to the benefits of bookkeeping, the forms and types of simple bookkeeping, how to record receipts and disbursements transactions, and perform profit and loss calculations. It is hoped that this service activity can continue to provide understanding and education for MSMEs about the importance of simple bookkeeping in order to increase the availability of MSME financial information in the midst of the Covid-19 pandemic.